ANALISIS HUKUM TERHADAP PEMBUBARAN BADAN USAHA MILIK DESA (BUM DESA) AMARTHA PATAS MELALUI MUSYAWARAH DESA DITINJAU BERDASARKAN PERATURAN PEMERINTAH NOMOR 11 TAHUN 2021 TENTANG BADAN USAHA MILIK DESA - Lubis, Muhammad Azmi Farid; Fachrurozi, Aal; Putra, Nouval Rivaldi; Fikri Fadhil, Muhammad; Hurruzia, Khansa; Gultom, Elisatris (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
Village-Owned Enterprises (BUM Desa) are legal entities that aim to manage and develop the potential of village resources as well as to improve the quality of life of village communities and strengthen village capabilities. However, its progress is certainly not easy, one of which is BUM Amartha Patas Village which has stopped operating after a three-year hiatus. Basically, BUM Desa cannot be dissolved and simply stops operating because this could give rise to other legal consequences. The management's responsibilities remain even though BUM Desa has been on hiatus for three years. This research is juridical-normative legal research aimed at finding and formulating legal arguments. This research has the characteristic of studying the object of legal research in terms of legal principles. The research results show that the responsibility of the BUM Desa management does not end with the cessation of business activities. They must complete all ongoing activities, settle the assets and obligations of BUM Desa, as well as protect community assets and settle debts. Cessation of business activities does not erase the legal status of BUM Desa as a legal entity. The dissolution of BUM Desa is defined as the cessation of business activities, with assets and liabilities remaining and must be handled legally.